COMBINED MODALITY TREATMENT FOR PATIENTS WITH INOPERABLE COLORECRAL LIVER METASTASES - A. V. Shabunin; M. M. Tavobilov; D. N. Grekov; P. A. Drozdov (Сибирский онкологический журнал)
The purpose of the study was to improve treatment outcomes for patients with inoperable colorectal liver metastases using the  combination of chemoembilization of the hepatic artery and radiofrequency ablation.Material and methods. Treatment outcomes of 60 patients with methachronic unresectable liver metastases from colorectal cancer  were analyzed. Eligibility criteria were as follows: absence of  extrahepatic metastases, size of metastases from 3 to 5 cm, and  inability to perform resection. All patients were divided into two groups. Group I included 30 patients who received combination  of regional chemotherapy and radiofrequency ablation. Group II (the control group) consisted of 30 patients who received radiofrequency ablation only.Results. Post-embolization and post-ablation syndromes were observed in both groups of patients. Rightsided hydrothorax  (Clavien-Dindo grade II) was found in 4 out of 60 patients (2  patients in Group I and 2 patients in Group II). One-, two- and  three-year disease-free survival rates in Group I patients were 96.6  %, 76.6 % and 53.3 %, respectively. The corresponding rates in the  control group patients were 90.0 %, 53.6 % and 30.0 %,  respectively (p=0.049). The overall one-, two-and three-year  survival rates in Group I patients were 100 %, 90 % and 63.3 %,  respectively. The corresponding rates in the control group patients  were 100 %, 70 % and 50.0 %, respectively (p=0.202).Conclusion. The combination of regional chemotherapy and radiofrequency ablation led to the improvement in overall and disease-free survival rates.